2023
DOI: 10.3390/ijms242015185
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Tri-Hydroxy-Methylated Chalcone Isolated from Chromolaena tacotana with Anti-Cancer Potential Targeting Pro-Survival Proteins

Gina Mendez-Callejas,
Marco Piñeros-Avila,
Juvenal Yosa-Reyes
et al.

Abstract: Chromolaena tacotana (Klatt) R. M. King and H. Rob (Ch. tacotana) contains bioactive flavonoids that may have antioxidant and/or anti-cancer properties. This study investigated the potential anti-cancer properties of a newly identified chalcone isolated from the inflorescences of the plant Chromolaena tacotana (Klatt) R. M. King and H. Rob (Ch. tacotana). The chalcone structure was determined using HPLC/MS (QTOF), UV, and NMR spectroscopy. The compound cytotoxicity and selectivity were evaluated on prostate, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 114 publications
0
3
0
Order By: Relevance
“…The induction of apoptosis by chalcones, particularly through the activation of caspase-3, is a well-documented phenomenon [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In our study, the data suggested that DDC preferentially activated caspase-3 over caspase-7 in MDA-MB-231 cells, as illustrated in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The induction of apoptosis by chalcones, particularly through the activation of caspase-3, is a well-documented phenomenon [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ]. In our study, the data suggested that DDC preferentially activated caspase-3 over caspase-7 in MDA-MB-231 cells, as illustrated in Figure 5 .…”
Section: Discussionmentioning
confidence: 99%
“…tacotana ) is an endemic plant in Colombia, a source of flavonoids with antiproliferative properties [ 26 ] that depends on the position of the hydroxyl groups in the molecule’s structure [ 27 ]. Recently identified flavonoids, such as 3′,4′-dihydroxy-5,7-dimethoxy-flavanone and 2′,3,4-trihydroxy-4′,6′-dimethoxychalcone, exhibit significant antiproliferative activity against cancer cells, particularly TNBC [ 28 , 29 ]. Chalcotanina induces autophagy by affecting the structural conformation of the mTOR protein and apoptosis through the activation of caspases 3/7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation